2011
DOI: 10.1007/s10689-011-9418-1
|View full text |Cite
|
Sign up to set email alerts
|

A clinical perspective on genetic counseling and testing during end of life care for women with recurrent progressive ovarian cancer: opportunities and challenges

Abstract: 10–15% of invasive epithelial ovarian cancer is attributable to hereditary breast and ovarian cancer. The identification of BRCA1/BRCA2 mutations in women with ovarian cancer allows for accurate predictive genetic testing of their at-risk relatives, who can then avail themselves of early detection and risk reduction strategies. In the case of women with recurrent progressive ovarian cancer, the window of opportunity for genetic testing can be particularly limited. Here we describe our perspective on providing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…In total, Search 1 identified 2424 records (Appendix S2). Title and abstract screening excluded 2379 records and the remaining 45 full‐text articles were retrieved and assessed for eligibility . This led to inclusion of 39 studies that used both quantitative and qualitative study designs.…”
Section: Resultsmentioning
confidence: 99%
“…In total, Search 1 identified 2424 records (Appendix S2). Title and abstract screening excluded 2379 records and the remaining 45 full‐text articles were retrieved and assessed for eligibility . This led to inclusion of 39 studies that used both quantitative and qualitative study designs.…”
Section: Resultsmentioning
confidence: 99%
“…Limited empirical studies have suggested that palliative patients knew little or nothing about genetics (Quillin et al 2008). However, anecdotal evidence suggests that palliative patients have deep concerns for the welfare of their families, including the worry that family members will also be affected by disease (Daniels et al 2011;Lillie 2006). This is similar to empirical evidence which examines the perceptions and opinions of non-terminal patients for whom a genetic link to disease would have no direct medical benefit.…”
Section: Introductionmentioning
confidence: 83%
“…Similarly to the literature, the view that genetic conversations should have taken place with other HCP before the point of palliative treatment was raised by most of the participants (Lillie et al 2011;Metcalfe et al 2010). Unlike the literature, this was not necessarily cited as a reason to not have these discussions, as participants acknowledged that it should not be assumed that it had been previously addressed, such has been previously argued by genetics professionals (Daniels et al 2011). Perhaps this healthy level of cynicism could be exploited by those providing training to this cohort.…”
Section: Implications For Practice: a Need For Further Trainingmentioning
confidence: 94%
See 1 more Smart Citation
“…Further research is needed on the most effective use of this genetic information in formulating counseling and clinical management strategies. Also, attention should be directed toward the provision of genetic counseling and testing during the end of life care [120][121][122].…”
Section: Discussionmentioning
confidence: 99%